Perancangan Penilaian Kinerja Karyawan Berdasarkan Kompetensi Spencer dengan Metode AHP dan Graphic Rating Scale dalam Menentukan Besaran Bonus Tahunan - Dwi Ufa Putri; Yan Orgianus; Hirawati Oemar (UNISBA Press, 2022)
Abstract. XYZ Cooperative is a cooperative engaged in retail. In addition to salary, employees as members of the cooperative get the remaining operating results and bonuses from the profits earned by the cooperative. Bonuses and the remaining operating results are distributed based on the employee's service period. Giving this bonus has not had an impact on employee performance, so it is necessary to find a more appropriate bonus distribution system in order to motivate employees to provide better performance. The purpose of this study was to identify the appropriate competence of Spencer to be used as an employee performance appraisal, to design an employee performance appraisal using the graphic rating scale method, to determine the amount of bonus for each employee. The AHP method is used to determine the priority weights on the criteria. While the graphic rating scale method is used to assess the performance of each employee. The assessment indicator uses Spencer's competence. Based on the results of the selection of questionnaires to experts, it was identified that there were nine indicators of employee performance appraisal of twenty Spencer competencies, namely 1) the ability to achieve enthusiasm, 2) the ability to focus on tasks, quality and thoroughness in work, 3) the ability to take initiative, 4) the ability to seek information, 5 ) ability to empathize, 6) the ability to be customer-oriented, 7) the ability to control themselves, 8) the ability to be confident and 9) the ability to commit to the organization. Employee performance appraisal scores are used as the basis for calculating employee bonuses. The bonuses distributed by employees ranged from Rp1,957,392 to Rp3,220,486. Abstrak. Koperasi XYZ merupakan koperasi yang bergerak dibidang ritel. Selain gaji, karyawan sebagai anggota koperasi mendapatkan sisa hasil usaha dan bonus dari keuntungan yang di peroleh koperasi. Bonus dan sisa hasil usaha di bagikan berdasarkan masa kerja karyawan. Pemberian Bonus ini belum berdampak pada kinerja karyawan sehingga perlu dicarikan sistem pembagian bonus yang lebih tepat agar dapat memotivasi karyawan untuk memberikan kinerja yang lebih baik. Tujuan penelitian ini adalah mengidentifikasi kompetensi Spencer yang sesuai untuk dijadikan penilaian kinerja karyawan, merancang penilaian kinerja karyawan dengan metode graphic rating scale, menentukan besaran bonus setiap karyawan. Metode AHP digunakan untuk menentukan bobot prioritas pada kriteria. Sedangkan metode graphic rating scale digunakan untuk menilai kinerja masing masing karyawan. Indikator penilaianya menggunakan kompetensi Spencer. Berdasarkan hasil pemilihan kuesioner kepada pakar diidentifikasi ada sembilan indikator penilaian kinerja karyawan dari dua puluh kompetensi Spencer yaitu 1) kemampuan semangat berprestasi, 2) kemampuan fokus terhadap tugas, kualitas dan ketelitian dalam kerja, 3) kemampuan berinisiatif, 4) kemampuan mencari informasi, 5) kemampuan berempati, 6) kemampuan berorientasi kepada pelanggan, 7) kemampuan pengendalian diri, 8) kemampuan percaya diri dan 9) kemampuan komitmen terhadap organisasi. Skor penilaian kinerja karyawan dijadikan sebagai dasar perhitungan bonus karyawan. Bonus yang dibagikan karyawan berkisar antara Rp1.957.392 hingga Rp3.220.486. Kata Kunci: Penilaian Kinerja, AHP, Graphic Rating Scale, Kompetensi Spencer